376 Awardee Talk - Prenatal transportation stress alters physiology of suckling Brahman calves as mediated by changes in DNA methylation. (5th December 2019) - Littlejohn, Brittni P; Price, Debbi M; Neuendorff, Don A; Carroll, Jeffery A; Vann, Rhonda C; Riggs, Penny K; Riley, David G; Long, Charles R; Welsh, Thomas H; Randel, Ronald D
Abstract: Mechanisms by which prenatal programming alters the developmental trajectory of biological systems in utero is of relevance to animal agriculture. We hypothesized that prenatally stressed (PNS) calves would exhibit altered postnatal phenotype and differential methylation of DNA. Mature Brahman cows (n = 48) were transported for 2-h periods at 60, 80, 100, 120, and 140 (± 5) d of gestation or maintained as non-transported Controls (n = 48). PNS calves exhibited more excitable temperaments and increased circulating concentrations of cortisol. In response to a glucose tolerance test administered to a subset of PNS and Control bulls, PNS calves returned to basal concentrations of insulin more rapidly and exhibited a lower total area under the insulin response curve. In response to a lipopolysaccharide challenge administered to a subset of PNS and Control bulls, PNS calves exhibited greater circulating concentrations of cortisol and a greater change from baseline for IFN-γ and monocytes. Reduced representation bisulfite sequencing was used to assess methylation of DNA from white blood cells in a subset of 28-d-old bull calves. Because increased methylation of DNA in a gene promoter region typically results in decreased transcriptional activity, differentially methylated CG sites located within promoter regions (n = 1, 205) were used to predict alterations to canonical pathways using Ingenuity Pathway Analysis software. There were 113 pathways altered (P ≤ 0.05) in PNS calves. Among these were pathways related to behavior, stress response, metabolism, and immune function. In support of our hypotheses, differential methylation in gene regions related to temperament, stress response, metabolism, and immune response corresponded to phenotypic differences observed in PNS calves, suggesting DNA methylation as a mechanistic basis for prenatal programming. The role of the prenatal epigenome in shaping postnatal outcomes provides novel opportunities to improve animal health and production traits.